Respuestas

2013-05-13T22:27:12+02:00

3(x+2) - 4 = 7 - x

 

3x + 6 - 4=7 - x     -----> despejamos x

 

3x + x = 7 + 4 -6

 

4x = 5

 

x = 5/4

 

 

5.5x + 3x - 2x = 15 - x ----> depejamos x

 

5x + 1/2x +3x - 2x + x = 15 -----> se descompuso 5,5

 

15/2x = 15

 

x = (15 *2)/15

 

x=2

 

 

2013-05-13T22:56:53+02:00

ejercicio 1

 

1)    3(x+2)-4=7-x

       3x+6-4=7-x

       3x+x=7-6+4

         4x=5

            x=5/4

 ejercicio 2

 

2) 5,5x+3x-2x=15-x

     5,5x+3x-2x+x=15

             7,5 x=15

      75 x= 15

      10

 x=10*15

        75

 

x=150

      75

 x= 2